Assessment of physical and sensory attributes of date-based energy drink treated with ultrasonication: modelling changes during storage and predicting shelf life - Fikry, Mohammad; Yusof, Yus Aniza; Al-Awaadh, Alhussein M.; Mohd Baroyi, Syahrul Anis Hazwani; Mohamad Ghazali, Nashratul Shera; Kadota, Kazunori; Mustafa, Shuhaimi; Abu Saad, Hazizi; Abdul Karim Shah, Nor Nadiah; Al-Ghamdi, Saleh (Multidisciplinary Digital Publishing Institute, 2023)
Sonication is a relatively new and eco-friendly method used to extend the shelf life of food products. This study aimed to investigate the effects of ultrasonication and thermal treatments on the physical and sensory properties of an energy drink made from dates during cold storage at 4 °C. The study compared the effects of ultrasonication for 20, 30, and 40 min at 50% amplitude with thermal treatment at 90 °C for 5 min, aiming to model the changes in properties of processed drinks over time and predict their shelf life by integrating quality attributes. The results showed that total soluble solids (TSS) and electrical conductivity (EC) were not affected by cold storage and did not differ significantly between sonicated, thermally processed, and untreated samples. However, significant differences in pH; L*, a*, and b* values; Chroma; and sensory attributes were detected among the sonicated, thermally processed, and untreated samples. The sensory properties of the sonicated samples for 30 and 40 min and the thermally processed samples remained acceptable for up to 21 days. The study also found a positive correlation between the pH and the sweetness of the drink, as well as between the L* value and the appearance of the drink. Based on these findings, the zero-order model was able to accurately describe the real values of pH, colour characteristics, and sensory properties. Furthermore, the predicted shelf life of the drink sonicated for 40 min was longer than that of the control and thermally processed drinks, based on the colour change and pH of the drink. These results could be beneficial for beverage manufacturers seeking to control the quality properties of their products during processing and storage.